Laser Treatment of Wood Surfaces for Ski Cores: An Experimental Parameter Study. (15th September 2013) - Petutschnigg, Alexander; Stöckler, Michael; Steinwendner, Florian; Schnepps, Julian; Gütler, Herwig; Blinzer, Johann; Holzer, Helmut; Schnabel, Thomas
Abstract : Recently, the production of skis with wooden cores has increased due to changes in customer awareness concerning ecological issues and rising raw material costs for mineral oil resources. The preparation of ski surfaces is one of the main expense factors in the production of skis. Thus, one perspective of the AMER SPORTS CORPORATION is to treat wood surfaces with laser beams to develop new aesthetic possibilities in ski design. This study deals with different laser treatments for samples from various wood species: beech, ash, lime, and spruce. The parameters investigated are laser beam intensity and number of laser points on the surface. To evaluate the aesthetic changes, the CIELab color measurements were applied. Changes in the main wood components were observed by the Fourier transform infrared spectroscopy (FTIR) using an ATR (attenuated total reflectance) unit. The results show that the laser treatments on wood surfaces have an influence on wood color and the chemical composition. Especially the intensity of laser beams affects the color changes in different patterns for the parameters observed. These findings will be useful to develop innovative design possibilities of wood surfaces for ski cores as well as for further product design applications (e.g., mass customization).